The opiate toxin of online gambling: a consumer behavior analysis of online gambling users' addiction levels - Farasa, Alifia; Hakim, Irfan; Suryawardani, Ameylia; Romadhona, Faradiba; Irdiana, Sukma (Central Research Institute for Agriculture (CeRIA), 2024)
The aim of this research is to identify the factors that influence online gambling addiction, the impact on online gambling addicts and how to deal with online gambling addicts on the behavior of online gambling consumers in Lumajang Regency. A descriptive research methodology with a qualitative approach was used to understand in depth the online gambling addiction behavior that occurs in Lumajang Regency. The research results show that online gambling addicts have been involved in online gambling games since 2023, the majority of online gambling addicts use slot play as their game. Their main drive to play is to make big profits early on, which in turn leads them to become trapped in an addiction of trying to repeat that success. Economic factors are the main trigger for them to participate in online gambling. The impact that people feel when playing online gambling is very significant, especially the negative impact that results in them being trapped in debt. The majority of the reasons they are in debt are curiosity and the desire to keep trying even if they experience defeat. Even in one day, they are able to spend a substantial amount of money playing online gambling. In the end, these people expressed a strong desire to stop the habit of playing online gambling because they felt it had a very influential impact on their lives